1999
DOI: 10.1038/7385
|View full text |Cite
|
Sign up to set email alerts
|

Oral gene delivery with chitosan–DNA nanoparticles generates immunologic protection in a murine model of peanut allergy

Abstract: Food allergy is a common and often fatal disease with no effective treatment. We describe here a new immunoprophylactic strategy using oral allergen-gene immunization to modulate peanut antigen-induced murine anaphylactic responses. Oral administration of DNA nanoparticles synthesized by complexing plasmid DNA with chitosan, a natural biocompatible polysaccharide, resulted in transduced gene expression in the intestinal epithelium. Mice receiving nanoparticles containing a dominant peanut allergen gene (pCMVAr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
567
1
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 1,048 publications
(581 citation statements)
references
References 28 publications
10
567
1
3
Order By: Relevance
“…Pre-formed polymeric systems for gene delivery have been administered subcutaneously, 10 intravenously, 14 intramuscularly, 11,15 or orally 16,17 with promising results. These systems used various techniques to fabricate delivery systems from biodegradable polymers.…”
Section: Figure 3 Seap Expression In Serum Following Administration Omentioning
confidence: 99%
“…Pre-formed polymeric systems for gene delivery have been administered subcutaneously, 10 intravenously, 14 intramuscularly, 11,15 or orally 16,17 with promising results. These systems used various techniques to fabricate delivery systems from biodegradable polymers.…”
Section: Figure 3 Seap Expression In Serum Following Administration Omentioning
confidence: 99%
“…16 In a promising study (published during the course of this work), chitosan-based formulations of pDNA encoding for the reporter gene beta-galactosidase gave a significant gene expression after intestinal installation, providing evidence that chitosan may, at least under certain conditions, be an effective gene delivery system in vivo. 17 More importantly, oral administration of the chitosan formulation carrying a plasmid that encodes a peanut allergen induced tolerance against peanut allergy in a challenge model. 17 However, this study conflicts with several other investigations, which have found chitosan to be a relatively inefficient gene delivery system in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…17 More importantly, oral administration of the chitosan formulation carrying a plasmid that encodes a peanut allergen induced tolerance against peanut allergy in a challenge model. 17 However, this study conflicts with several other investigations, which have found chitosan to be a relatively inefficient gene delivery system in vitro and in vivo. 18,19 Thus, the factors that determine the effectiveness of chitosan-based gene delivery systems need to be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies suggest that flash nanocomplexation may be particularly suitable for the manufacturing of these NPs 36, 37. It has been 20 years since the first report suggesting the feasibility of using nonviral vectors to generate a therapeutic effect through oral administration 7. The ensuing years have only produced promise plagued by modest efficacy and low reproducibility.…”
Section: Discussionmentioning
confidence: 99%
“…Chitosan (CS) is an attractive gene carrier because of its low toxicity to cells7 and tunable physicochemical characteristics. Varying the molecular weight ( M W ) and degree of deacetylation (DA) of CS can yield a polysaccharide with different biodegradability and charge density at physiological pH.…”
Section: Introductionmentioning
confidence: 99%